The impact of a social support program in Immokalee, Florida, during the COVID-19 pandemic - Lindsay Richards; Leping Wang; Joashilia Jeanmarie; Shirin Shafazand; Daniel Palazuelos; Vitina Monacello (Healthcare in Low-resource Settings)
Farmworkers were considered “essential” during the COVID-19 pandemic, but face structural inequalities that heightened their risk of the pandemic’s health and economic impacts. This study aims to evaluate the impact of a COVID-relief cash transfer program in the farmworking community of Immokalee, Florida. The authors conducted 153 structured interviews with program beneficiaries via phone call or home visit and asked about sociodemographic variables, how the money was used, whether the money was sufficient for two weeks' financial needs, and participant ability to self-isolate. This study found that the cash transfers were most likely to be spent on living necessities and were effective in relieving COVID 19-associated financial burden, but that some groups may need more support than others. Given that the COVID-19 pandemic has exacerbated pre-existing health disparities, it is important to understand the role of cash transfers as a public health tool and their potential impact on community mitigation efforts.